The Effectiveness of Nigella Sativa Alcoholic Extract on the Inhibition of Candida Albicans Colonization and Formation of Plaque on Acrylic Denture Plates: an In Vitro Study - Hafez Ariamanesh; Nasim Tamizi; Alireza Yazdinezhad; Shilan Salah; Nima Motamed; Saeid Amanloo (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Due to growing concerns on complications of chemical drugs, the use of herbal extracts has been considered as denture cleaning solutions. Purpose: The aim of this study was to evaluate the in-vitro effects of Nigella sativa on the cleansing of the formation of Candida albicans plaque on the acrylic resin pieces. Materials and Method: In this experimental study, 30 pieces of acrylic resin were contaminated by Candida albicans suspension. Then, the acrylic pieces were randomly divided into six groups and treated with 0.2, 0.4, 20, and 200 mg/ml of Nigella sativa, 100,000 units of nystatin (positive control), and distilled water (negative control) for 8 hours. At the end of the exposure period of the drugs, the rinse solution from acrylic pieces was cultured in Sabouraud Dextrose Agar and the average of the colonies from each group was compared. Results: The average number of colonies obtained at concentrations of 0.2, 0.4, 20, and 200 mg/ml of Nigella sativa were 122.6, 117.8, 73.4, and 14.4 colonies, respectively, as compared to distilled water (141.6) and nystatin (0) that had a significant difference (p< 0.001). Conclusion: Nigella sativa extract at definite concentration is capable of clearing dental prosthesis, but compared to nystatin, it is weaker. However, due to the indirect immune-regulatory effects of Nigella sativa, it is suggested that other studies be conducted to investigate the therapeutic properties of Nigella sativa from the aspects of antimicrobial, anti-inflammatory, and oral ulcer healing in candida oral lesions.